The mystery hideout - Follett, Ken; Marchesi, Stephen (New York Morrow Junior Books, 1990)
Exploring in an old unused film studio, two boys run across clues to a series of unsolved bank robberies.
Previously published as: The secret of Kellerman's studio.
Keywords: Mystery and detective stories